Keefektifan Model Example Non Example dengan Pendekatan Saintifik untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa SD Negeri Gondoriyo - Istiqomah, Arina Nurul; Rizqi, Hesti Yunitiara (Universitas PGRI Semarang, 2024)
This research aims to find out how effective the example non example model is with a scientific approach to improve students' problem solving abilities. The subjects in this research were students in classes III A and III B at SDN Gondoriyo. The type of data in this research is quantitative with an experimental method in the form of purposive sampling. Data collection techniques in this research are Test (Pretest and Posttest) and Non Test (Observation, Questionnaire and Documentation). The data analysis techniques in this research are normality test, homogeneity test, hypothesis test in the form of Independent Sample T-test, simple linear regression test, and Paired Sample T-Test. The results of the research show that: (1) There is a difference in the use of the example non example model with a scientific approach towards students' problem solving abilities, as evidenced by the average value of the experimental class being higher than the control class, namely 75.35 62.82 and a significant value in the class. control and experimental class is 0.001 0.05. (2) There is an influence of using the example non example model with a scientific approach on students' problem solving abilities, as evidenced by the significance value of 0.001 0.05. (3) There is an increase in students' problem solving abilities in the example non example model with a scientific approach, as evidenced by the significance value of 0.001 0.05 that there is a real difference between the results of the pretest and posttest and the average results of the pretest and posttest of the experimental class shows 75.35 88.35. So it can be concluded that there is an increase in the Non-Example model with a scientific approach to students' problem solving abilities.